Gravimetric adsorption measurements of helium on natural clinoptilolite and synthetic molecular sieves at pressures up to 3500 kPa - Arami-Niya, Arash; Rufford, T.E.; Birkett, G.; Zhu, Z. (ELSEVIER, 2017)
We report helium adsorption capacities and the true specific impenetrable solid volumes of a clinoptilolite-rich Escott zeolite from Werris Creek (Australia), synthetic 3A and 4A zeolites, and carbon molecular sieve 3K-172 measured by a gravimetric method at pressures of (300–3500) kPa and temperatures in the range of (303–343) K. Our helium adsorption procedure extends the previous works by Gumma and Talu [1] to determine the impenetrable solid volume of the adsorbent, which in standard helium pycnometry is determined under the assumption that helium does not adsorb at room temperature. Our results confirm helium adsorption on these solids is small, but not zero: equilibrium helium adsorption capacities measured at 3500 kPa and 303 K were 0.067 mmol/g on Escott, 0.085 mmol/g on 3A, 0.096 mmol/g on 4A and 0.089 mmol/g on 3K-172. The specific solid volumes determined by the Gumma and Talu method were 10–15% larger than the specific solid volumes measured by standard helium pycnometry, and this error can result in uncertainties of 2.6–28% in the equilibrium adsorption capacities of CO2 and N2 measured at high pressures. The uncertainties were largest for N2 on the Escott zeolite, which had the lowest equilibrium adsorption capacity for N2. These results support the need to consider helium adsorption in the characterisation of adsorbents with narrow pore sizes, especially for adsorption processes that involve helium separations at low temperatures and/or high pressures.